The Spectrum of Clinical Symptomatology in Patients with Neuro-Behcet’s Disease - Liaqat, Jahanzeb; Muhammad, Wasim Wali; Arif, Saeed; Hashmat, Asif; Alamgir, Wasim (Pakistan Armed Forces Medical Journal, 2022)
Objective: To understand the pattern of neurological symptoms in patients diagnosed with Neuro-Behcet's disease.Study Design: Cross-sectional study.Duration and Place of Study: Pak Emirates Military Hospital Rawalpindi, from Jun 2013 to Jun 2018.Methodology: Cases diagnosed with Behcet's disease (BD) based on international criteria for Behcet's diseases (ICBD) were considered. Those cases of BD who presented with certain neurological manifestations were further analyzed for clinical symptomatology regarding the type of neurological symptoms. Moreover, data include cerebrospinal fluid (CSF) analysis, laboratory tests, and magnetic resonance imaging (MRI) findings.Results: A total of 79 cases fulfilled the ICBD diagnostic criteria. The mean age of the cases was 36.78 ± 11.85 years. Central nervous system involvement occurred in 46 (58.2%) cases. Out of 46 patients with Neuro-Behcet's disease (NBD) with central nervous system manifestations, non-parenchymal involvement was common in 23 (50%) patients compared to parenchymal involvement in 16 (34.8%) patients. Among neurological features, migraine-like headaches were the most common manifesttation present in 29 (36.7%) patients with Behcet's disease. The stroke-like presentation occurred in 18 patients, while 16 casesmanifested with seizures clinically. Migraine like headaches, stroke-like episodes, seizures and neuropsychiatric features were significantly more common among patients with Neuro-Behcet's disease. Out of 46 patients with central nervous system involvement, MRI brain findings were present in 34 (73.91%) cases.Conclusion: Behcet's disease can manifest with various symptoms, including a wide range of neurological involvement. Understanding such neurological manifestations can result in early recognition and treatment of this relatively aggressive and resistant auto-immune disease.